Multiplexed Visualization Method to Explore Complete Targeting Regulatory Relationships Among Circadian Genes for Insomnia Treatment - Li, Tao; Liu, Zhenyu; Wang, Yitong; Zuo, Dongshi; Wang, Shenyuan; Ju, Haitao; Wang, Shichao; Xing, Yanping; Ling, Yu; Liu, Chunxia; Zhang, Yanru; Zhou, Huanmin; et al. (Frontiers in Neuroscience, 2022)
Understanding the complete map of melatonin synthesis, the information transfer network among circadian genes in pineal gland, promises to address outstanding questions in endocrine systems biology and improve the diagnosis and therapeutic of insomnia, immune disease and hysterical depression. Currently, some landmark studies have revealed some genes that regulate circadian rhythm associated with melatonin synthesis. However, these studies fail to provide a complete map of melatonin synthesis, as transfer information among circadian genes in pineal gland is lost. New biotechnology, integrates dynamic sequential omics and multiplexed imaging method, has been used to visualize the complete process of melatonin synthesis. It is found that there are two extremely significant information transfer processes involved in melatonin synthesis. In the first stage, as the light intensity decreased, melatonin synthesis mechanism has started, which is embodied in circadian genes, Rel, Polr2A, Mafk and Srbf1 become active. In the second stage, circadian genes Hif1a, Bach1, Clock, E2f6 and Per2 are regulated simultaneously by four genes, Rel, Polr2A, Mafk and Srbf1 and contribute genetic information to Aanat. The expeditious growth in the technique promises to yield a more comprehensive understanding of gene-to-gene variation among circadian genes in pineal gland. Here we provide the current state and future perspectives on the new method expected to drive the next generation of research and diagnostic and therapeutic the disease associated with melatonin synthesis disorder.